The Effectiveness of Using Story Mapping on Students™ Reading Comprehension at Ninth Grade of SMP 14 Tangerang - Salma, Intan Puspita (Universitas Negeri Medan, 2024)
The aim of this research is to find the effectiveness of using story mapping toward students reading comprehension used theme fairy tales on narrative text in SMP 14 Kota Tangerang. The method in this research used quasi experimental design. The sample of this research is cluster random sampling. The population of this research was ninth grade of SMP 14 Kota Tangerang. The research took 2 classes as an experimental and control class. Each class consists of 25 students. The technique used in data collection was test, which were 20 items of multiple choice to measure the understanding of students reading comprehension. The results showed pre-test mean in control class is 77,80 and pre-test mean in experimental class is 82,40. The post-test mean in control class is 74,40 and post-test mean in experimental class is 79,60. The researcher found that students who got higher score 90 in the experimental class on the pre-test exam was (28%), and the pre-test exam in control class was (12%), meanwhile the experimental on the post-test exam was (12â„…) and post-test exam on control class was (8%). The collected data were analyzed by using SPSS version 26. The calculation results of t-test showed that Tcount > Ttabel, 2.181 > 1.677, The degree of freedom (df) is 48 and the value of significant 0.05 (5%) the value of degree significant is 1.677. It can be said that Alternative Hypothesis (Ha) was accepted and the Null hypothesis (H0) was rejected. it means that the use of story mapping on students reading comprehension at ninth grade was considered effective on narrative text used theme fairy tales.